Image-Guided Bone Consolidation in Oncology - Buy, Xavier; Catena, Vittorio; Roubaud, Guilhem; Crombe, Amandine; Kind, Michèle; Palussiere, Jean (Seminars in Interventional Radiology, 2018)
Occurrence of bone metastases is a common event in oncology. Bone metastases are associated with pain, functional impairment, and fractures, particularly when weight-bearing bones are involved. Management of bone metastases has been improved by the development of various interventional radiology consolidation techniques. Cementoplasty is based on injection of acrylic cement into a weakened bone to reinforce it and to control pain. This minimally invasive technique has proven its efficacy for flat bone submitted to compression forces. However, resistance to torsion forces is limited and, thus, treatment of long bones should be considered with caution. In recent years, variant techniques of percutaneous bone consolidation have emerged, including expansion devices for vertebral augmentation and percutaneous screw fixation for pelvic bone and proximal femur tumors. Research projects are ongoing to develop drug-loaded cements to use them as therapeutic vectors. However, release of drugs is still poorly controlled and conventional polymethylmethacrylate cement remains the gold standard in oncology. Image-guided consolidation techniques enhance the array of treatments in bone oncology. Multidisciplinary approach is mandatory to select the best indications.
Keywords: cementoplasty; vertebroplasty; bone metastasis; screw fixation; interventional radiology